English Competence of Conversational Interaction between Teachers and Students in Classrooms - Toan, Ly Ngoc (Pascasarjana Universitas Negeri Makassar, 2024)
The main goal of this study is to improve the ability of teachers and students to converse in English in high schools in the province of Dong Nai. The study framework is based on the sociocultural theory of Vygotsky, with additional contributions from Long's interaction theory and Brown's communicative English teaching methodology. The research findings show that the four factors including belonging, expectation, relationship, and motivation have a positive and statistically significant impact on the conversational English-language interactions between teachers and students in this educational context. These findings were obtained through a survey of 148 English teachers in high schools located in Dong Nai and subsequent data analysis using SPSS 20 software. The study's findings led the researchers to suggest a number of workable methods for improving teachers' ability to converse with learners in English. These kinds of initiatives are expected to have a major role in improving the quality of education as a whole, bringing it into compliance with international norms, and encouraging increased competition with industrialized countries in the area. The aforementioned undertaking signifies a deliberate attempt to further progress language learning in Vietnam.